The First Description Of Germ Tube Fusion Body In Germinating Basidiospores Of Exobasidium Vexans - Mohktar, Norsyuhada; Nagao, Hideyuki (2017)
Germ tube fusion body (GFB) is known to allow for anastomosis between contacting germ tubes in germinating urediniospores of rust fungi in the genus PUCCINIA (Wang and McCallum, 2009).